2017
DOI: 10.1111/1348-0421.12498
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the cell tropism of serotype 1 feline infectious peritonitis virus using the spike affinity histochemistry in paraffin‐embedded tissues

Abstract: Unlike for serotype II feline coronaviruses (FCoV II), the cellular receptor for serotype I FCoV (FCoV I), the most prevalent FCoV serotype, is unknown. To provide a platform for assessing the pattern by which FCoV I attaches to its host receptor(s), HEK293 cell lines that stably express the ectodomains of the spike (S) proteins derived from a FCoV I feline enteric coronavirus strain UU7 (FECV UU7) and a feline infectious peritonitis virus strain UU4 (FIPV UU4) were established. Using the recombinant S protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…The increased virus infection of Fcwf-4 CU cells could be due to any number of cellular factors; however, it is tempting to speculate that the reduced IFN-responsiveness of the Fcwf-4 CU cells relative to the Fcwf-4 ATCC cells may significantly enhance infection in the former. Further, these Fcwf-4 CU cells may express a higher density of the yet unknown type I virus receptor (Cham et al, 2017; Dye et al, 2007) and therefore may be critical in identifying the receptor or other cellular characteristics that allow for enhanced type I virus replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased virus infection of Fcwf-4 CU cells could be due to any number of cellular factors; however, it is tempting to speculate that the reduced IFN-responsiveness of the Fcwf-4 CU cells relative to the Fcwf-4 ATCC cells may significantly enhance infection in the former. Further, these Fcwf-4 CU cells may express a higher density of the yet unknown type I virus receptor (Cham et al, 2017; Dye et al, 2007) and therefore may be critical in identifying the receptor or other cellular characteristics that allow for enhanced type I virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical that we investigate type I FIPV in laboratory cell culture in order to understand the basic virology of natural infection, characterize type I clinical isolates, test novel therapeutics, and develop effective feline vaccines with broader coverage. However, this has been challenging because type I FCoVs cannot be easily adapted to laboratory cell culture; furthermore, the receptor for type I is not known (Cham et al, 2017; Dye et al, 2007; Hohdatsu et al, 1998), making the identification of highly permissive cell types difficult. Select type I isolates, such as the FIPV Black strain used in this study, have been adapted to growth in tissue culture at the cost of reduced in vivo virulence (Black, 1980; Pedersen, 2009; Tekes et al, 2007; Thiel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…FCoV replication starts with the attachment of the virion to the host cell membrane (Fig. 2) (Cham et al, 2017). The interaction between the virus and the cell is first accomplished by binding the viral S protein to the receptor in the cellular membrane.…”
Section: Replicationmentioning
confidence: 99%
“…The interaction between the virus and the cell is first accomplished by binding the viral S protein to the receptor in the cellular membrane. This interaction is key to the determination of viral tropism and host range (Balint et al, 2012;Cham et al, 2017;Lai, 1990). Receptor usage by CoVs has been studied for several years and protein and glycan cellular receptors have been reported for different CoVs (Table 2).…”
Section: Replicationmentioning
confidence: 99%
“…However, the in vitro propagation of FIPV I isolates in tissue culture systems has proven to be problematic, impeding forward progress in tissue-culture-based virology and pathogenesis investigations. While the primary cellular receptor utilized for cell entry by FIPV II has been identified as feline aminopeptidase N (feAPN/CD13), the primary cellular receptor utilized by FIPV I remains to be determined [ 16 , 17 , 18 , 19 ]. There are conflicting results regarding the possibility of feAPN serving as a primary cell receptor for FIPV I. Tresnan et al (1996) found that non-permissive mouse or hamster cells, transduced to stably express feAPN, became permissive to both FIPV I and II replication [ 16 ].…”
Section: Introductionmentioning
confidence: 99%